Fuzzy Neo: A Novel Method for Batch Liquid Temperature Control System Using Simpler Fuzzy Rule and Inference - Borneo Satria Pratama; Arya Dwicahya S; Gary Christ Noviardo Sihombing; Alfiqriyansyah; Nilandra Ayu Az-Zahra (Metrotech (Journal of Mechanical and Electrical Technology), 2023)
Industries and laboratories heavily rely upon temperature-controlling technology due to the dependencies of their systems on temperature stability. Therefore, temperature control systems were implemented to maintain the stability of the temperature in those systems, including the batch processes. This research aimed to propose and test a novel method for batch liquid temperature control system using Fuzzy Neo which has simpler fuzzy rule and inference compared to the previous methods. The system was developed using an Arduino-based microcontroller to control the heating process of water. The results showed that the implementation of Fuzzy Neo was successfully stabilizing and maintaining the temperature in the system from different temperature references and adapted against the disturbance simulated to the system. The value of RMSE is 0.5347, which showed that the observed value of dimmer frequencies in the system are close to the predicted values calculated using Fuzzy Neo method.